A Literature Review on Vertical Adaptation Of Fixed Implant-Supported Prostheses: Conventional System Versus Cad/Cam System - Rafaela Regina de Lima; Jader Oliva Jorge; Barbara Magalhães Figueiredo Dias; Laura Silva Jerônimo; Eduardo Fraiha Henriques; Frederico Santos Lages; Ricardo Rodrigues Vaz (Archives of Current Research International, 2025)
Aims: The present study aims to review the literature on the vertical adaptation of fixed implant prostheses, made by the conventional system and the CAD/CAM system. Place and Duration of Study: The study was carried out at a training center for dentistry specialists in Belo Horizonte, Brazil, during 2022. Methodology: The methodology of this study consisted of a bibliographic search carried out in the main scientific databases in order to identify relevant publications on the vertical adaptation of implant-supported fixed prostheses. The search strategy employed keywords in both English and Portuguese, including Dental implants, Dental prosthesis fixed implant, and Prostheses and implants, combined through the Boolean operators AND and OR to optimize the retrieval of articles. Results: The results revealed a better vertical adaptation in the use of CAD/CAM systems to obtain fixed prosthesis on implant when compared to conventional techniques and provided greater passivity for the fixed prosthesis/implant set, consequently better distribution of stresses on bone structures. Conclusion: CAD/CAM systems for implant-supported fixed prostheses demonstrated superior vertical adaptation compared with conventional techniques, as well as greater passivity of the prosthesis–implant complex, resulting in improved stress distribution on the bone structures.